1992
DOI: 10.1159/000175026
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Effects and Pharmacokinetics of Long-Term Therapy with Ibopamine in Patients with Chronic Heart Failure

Abstract: To evaluate the attenuation of the effectiveness of long-term ibopamine therapy, ibopamine was administered in single doses of 100 and 200 mg to 10 patients with chronic heart disease. The hemodynamic studies using Swan-Ganz catheter and pharmacokinetic studies were carried out. Ibopamine was found to increase cardiac output and stroke index and to decrease systemic vascular resistance in this acute study. Six patients underwent long-term therapy with the drug and were evaluated for the development of toleranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This hypothesis has been supported by an invasive study examining the changes in myocardial mechanics produced by plasma epinine concentrations comparable to those achieved after administration of therapeutic oral doses of ibopamine (l00 to 200mg) [Rousseau et al 1992]. Haemodynamic effects of oral ibopamine, administered as a single dose in patients at rest with moderate to severe congestive heart failure Reference De Vita et al (1986) Dei Cas et al (1992) Oi Mario et al (1990) Green et al Itoh et al (1992) Metra et al Morimoto et al (1989) Reffoetal. Haemodynamic effects of oral ibopamine, administered as a single dose in patients at rest with moderate to severe congestive heart failure Reference De Vita et al (1986) Dei Cas et al (1992) Oi Mario et al (1990) Green et al Itoh et al (1992) Metra et al Morimoto et al (1989) Reffoetal.…”
Section: Central Haemodynamic Effectsmentioning
confidence: 93%
See 1 more Smart Citation
“…This hypothesis has been supported by an invasive study examining the changes in myocardial mechanics produced by plasma epinine concentrations comparable to those achieved after administration of therapeutic oral doses of ibopamine (l00 to 200mg) [Rousseau et al 1992]. Haemodynamic effects of oral ibopamine, administered as a single dose in patients at rest with moderate to severe congestive heart failure Reference De Vita et al (1986) Dei Cas et al (1992) Oi Mario et al (1990) Green et al Itoh et al (1992) Metra et al Morimoto et al (1989) Reffoetal. Haemodynamic effects of oral ibopamine, administered as a single dose in patients at rest with moderate to severe congestive heart failure Reference De Vita et al (1986) Dei Cas et al (1992) Oi Mario et al (1990) Green et al Itoh et al (1992) Metra et al Morimoto et al (1989) Reffoetal.…”
Section: Central Haemodynamic Effectsmentioning
confidence: 93%
“…Many studies have shown ibopamine to have no significant proarrhythmic activity (Dei Cas et al 1988;Fazio et al 1990;Fonseca et al 1989;Man in' t Veld 1990;van Veldhuisen et al 1990a), although some studies have reported an increase in premature ventricular contractions and arrhythmia in small numbers of patients (n = 1 to 5) during ibopamine therapy Cavalli et al 1989;Ghiringhelli et al 1990;Itoh et al 1992;Kayanakis et al 1991;Partanen et al 1988). However, in 2 of these trials, ventricular arrhythmia was present in most patients at baseline Ghiringhelli et al 1990).…”
Section: Tolerabilitymentioning
confidence: 99%
“…At a systemic level, low-dosage ibopamine does not affect the arterial pressure during either the short or the long term [33,35,36]. In our study no significant pressure differences were found between the two groups during the observation period.…”
Section: Discussionmentioning
confidence: 49%
“…Ibopamine is an orally active dopamine agonist which has been shown to activate dopaminergic receptors DA1 and DA2 at daily doses of 100-200 mg, β-adrenergic receptors at 300-400 mg, and α-adrenergic receptors at greater than 400 mg. 6,7 Its pharmacological effect is maintained over prolonged periods. 8,9 Both in normal subjects and in patients with mild renal impairment, ibopamine administration has produced an increase in renal plasma flow, an increase in 99m Tc-DTPA clearance, a reduction in filtration fraction and an increase in sodium excretion and diuresis. [10][11][12] Stefoni et al 2 conducted a prospective, randomised, open-label, multicentre trial of ibopamine in patients with mild-to-moderate chronic kidney disease CKD (plasma creatinine 1.5-4.0 mg/dL).…”
Section: Ibopaminementioning
confidence: 99%
“…The latter point may be particularly relevant since ibopamine has been shown to exert an antagonistic effect against angiotensin II at both a glomerular and tubular level. 8,13 It also directly reduces activation of the renin-angiotensin system and inhibits aldosterone secretion. [14][15][16] Three prospective, non-controlled, small studies by single centres [3][4][5] have reported a significant improvement in renal function indices (plasma creatinine, reciprocal plasma creatinine or creatinine clearance) in patients with mild-tomoderate CKD treated with ibopamine 100 mg daily for periods ranging from 6 to 24 months.…”
Section: Ibopaminementioning
confidence: 99%